The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae) - Shimada, Kenshu; Egi, Naoko; Tsubamoto, Takehisa; Maung-Maung, Maung-Maung; Thaung-Htike, Thaung-Htike; Zin-Maung-Maung-Thein, Zin-Maung-Maung-Thein; Nishioka, Yuichiro; Sonoda, Teppei; Takai, Masanaru (Zootaxa, 2016)
We redescribe an extinct river shark, Glyphis pagoda (Noetling), on the basis of 20 teeth newly collected from three different Miocene localities in Myanmar. One locality is a nearshore marine deposit (Obogon Formation) whereas the other two localities represent terrestrial freshwater deposits (Irrawaddy sediments), suggesting that G. pagoda from the Irrawaddy sediments was capable of tolerating low salinity like the extant Glyphis. Glyphis pagoda likely reached up to at least 185 cm in total body length and was probably piscivorous. The fossil species occurs in rocks of Myanmar and eastern and western India and stratigraphically ranges at least from the Lower Miocene (Aquitanian) to the lower Upper Miocene (mid-Tortonian). It has been classified under at least eight other genera to date, along with numerous taxonomic synonyms largely stemming from the lack of understanding of the heterodonty in extant Glyphis in the original description. Our literature review suggests that known Miocene shark faunas, particularly those in India, are manifested with unreliable taxonomic identifications and outdated classifications that warrant the need for a comprehensive taxonomic review in order to evaluate the evolutionary history and diversity pattern of Miocene shark faunas. The genus Glyphis has a roughly 23-million-year-long history, and its success may be related to the evolution of its low salinity tolerance. While extant Glyphis spp. are considered to be particularly vulnerable to habitat degradation and overfishing, the fossil record of G. pagoda provides renewed perspective on the natural history of the genus that can be taken into further consideration for conservation biology of the extant forms.